THE SPEECH STYLES OF A PASTOR IN A PUBLIC ANDA YOUTH SERVICE - Evalia Ester Uniplaita; Samuel Gunawan (Kata Kita: Journal of Language, Literature, and Teaching, 2014)
This researched focused on the observation about the speech styles used by a Pastor in delivering the sermon in a Public Service and a Youth Service. In order to know the characteristics of speech styles used by the Pastor, this writer chooses the main theory of formal and informal Bahasa Indonesia as proposed by Tampubolon (1978) which are supported by the theory of lexical and grammatical characteristics for standard Bahasa Indonesia by Kridalaksana (1989). As results, this research shows that the Pastor mostly used informal style in both services because she wanted to more get closer with the Public and Youth Service congregation. However, the Pastor tended to use more formal style to the Public Service congregation than to the Youth Service congregation because she knew exactly that the Youth Service was supposed to be given more attention and clearer explanation about the message given.